Bicycling magazine's training techniques for cyclists : greater power, faster speed, longer endurance, better skills - Hewitt, Ben, 1971- (Rodale ; Distributed to the trade by Holtzbrinck Publishers, 2005)
Revised and updated to incorporate the latest advances in the sport, a detailed training guide features ways to achieve optimum cycling performance, with exercises designed to improve one's overall cycling fitness, a twenty-six-week training regimen, and winter training programs to keep one fit in the off-season.